A new mix design method for low-environmental-impact blended cementitious materials: Optimization of the physical characteristics of powders for better rheological and mechanical properties. (April 2022) - Ahmadah, Oumayma; Bessaies-Bey, Hela; Yahia, Ammar; Roussel, Nicolas
Abstract: The use of blended cements has attracted much interest in the quest to overcome the environmental challenges facing the concrete industry. However, partially replacing cement with supplementary cementitious materials (SCMs) can result in complex rheological behavior that is influenced by the type of SCM and the replacement percentage, as well as the physical characteristics of the particles. Adequate physical control of the blended cements is essential for improving the rheology of the suspensions. A new mix design methodology based on the physical optimization of SCMs is proposed and validated to ensure adequate rheology of the suspensions. The physical characteristics that influence the viscosity of the cement-based suspensions investigated in this study include particle-size distribution, surface roughness, maximum packing density of the powder, and interparticle distance. Based on the experimental results presented in this paper, ternary binders with optimized physical characteristics enhanced the 28-day compressive strength of mortar by 20% while decreasing the clinker content by 15% and maintaining constant fluidity.